Type 2 Diabetes Mellitus: Physiological and genetic aspects and the use of physical exercise for diabetes control. - Gisela Arsa; Laila Lima; Sandro Soares de Almeida; Sérgio Rodrigues Moreira; Carmen Sílvia Grubert Campbell; Herbert Gustavo Simões (Universidade Federal de Santa Catarina, 2009)
Type 2 Diabetes mellitus (DM2) is a metabolic disease Type 2 Diabetes mellitus (DM2) is a metabolic disease characterized by hyperglycemia and cardiovascular dysfunctions that can be controlled with physical exercise, dietary control and pharmacological treatment. Recent research has demonstrated associations between DM2 and some genetic polymorphisms, especially alterations to the gene that codes for Angiotensin Converting Enzyme (ACE). The purpose of this study was to discuss the pathophysiology of DM2 and the use of physical exercise as a non-pharmacological method for controlling these patients' glycemia and blood pressure. The relationship between DM2 and polymorphisms of the ACE gene was also covered. The literature search included textbooks in the healthcare field in addition to review articles and original articles found on the databases Pubmed, Scielo and Portal Capes. Keywords used were "blood glucose", "type 2 diabetes", "exercise", "blood pressure" and "ACE gene polymorphism" and their translations in Portuguese. The main subject of this article is the practice of daily exercise, the types and intensities that have proven effective for glycemic and haemodinamic control and possible relationships with the ACE polymorphism, which are currently still tentative, since the evidence of associations can be strongly influenced by the population studied. The benefits of exercise are unquestionable and the recommended forms are discussed in this review. However the literature is still lacking studies that analyze the effects of physical exercise on diabetics and take into account the relationship with genetic aspects. This area is evidently an appropriate subject for further research.